2018
DOI: 10.1159/000488188
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ischemia Modified Albumin as a Biomarker in Acute Ischaemic Stroke

Abstract: Background and Purpose: Stroke is one of the leading causes of mortality and long-term disability. Prompt diagnosis and treatment of stroke are crucial for a better outcome. A blood test, which serves as a biomarker in rural areas will help in immediately transferring patients to a hospital for thrombolytic therapy. The aim of the present study was to examine the role of ischemia modified albumin (IMA) as a screening biomarker in acute ischaemic stroke. Materials and Methods: Serum samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…However, some studies showed that the levels of IMA may be diverse in different ischemic conditions such as stroke, mesenteric ischemia and different types of cancer. [9][10][11] We hypothesized that a newly developed practical and inexpensive method 'dynamic TD homeostasis' and IMA can be evaluated in the serum of patients with cervical cancer in conjunction with current diagnostic tests. Herein, our objective is to evaluate whether there is a difference between cervical cancer patients and healthy individuals by means of dynamic TD homeostasis, IMA and other oxidative stress parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies showed that the levels of IMA may be diverse in different ischemic conditions such as stroke, mesenteric ischemia and different types of cancer. [9][10][11] We hypothesized that a newly developed practical and inexpensive method 'dynamic TD homeostasis' and IMA can be evaluated in the serum of patients with cervical cancer in conjunction with current diagnostic tests. Herein, our objective is to evaluate whether there is a difference between cervical cancer patients and healthy individuals by means of dynamic TD homeostasis, IMA and other oxidative stress parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia modified‐albumin (IMA) is a biochemical test used in cases that may cause an acute ischemic condition such as acidosis, free radical damage and hypoxia. However, some studies showed that the levels of IMA may be diverse in different ischemic conditions such as stroke, mesenteric ischemia and different types of cancer 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Ischemia-modi ed albümin (IMA) is the altered form of albumin as a result of oxidative stress and is de ned as a new marker used in determining ischemic events [24]. Although IMA was rst de ned as a myocardial ischemic marker, studies have shown that it increases in non-cardiac oxidative stress and ischemia states, such as cerebrovascular diseases, in ammatory diseases, pulmonary embolism, and chronic liver diseases [24][25][26][27][28]. Besides, the thiol/disul de balance developed by Erel et al is used to evaluate the oxidant/antioxidant balance in oxidative damage [29].…”
Section: Introductionmentioning
confidence: 99%
“…IMA is accepted as a marker of oxidative stress, ischemia and endothelial disfunction. There are several recent studies that point to the relationship between IMA and infections, cardiovascular diseases and stroke . IMA levels have also been evaluated in some inflammatory and rheumatological diseases such as rheumatoid arthritis and Behçet's disease .…”
Section: Introductionmentioning
confidence: 99%
“…There are several recent studies that point to the relationship between IMA and infections, cardiovascular diseases and stroke. [14][15][16][17] IMA levels have also been evaluated in some inflammatory and rheumatological diseases such as rheumatoid arthritis and Behçet's disease. 18,19 The Birmingham Vasculitis Activity Score (BVAS) is a validated tool for assessment of disease activity in patients with many different forms of vasculitis.…”
Section: Introductionmentioning
confidence: 99%